Ancient Neurilemoma of the Lower Lip Mimicking Malignancy: A case report with Histopathologic Challenge (Bangladesh Journal of Medical Science, 2026)
Neurilemoma, also known as Schwannoma, is a slowgrowing, benign tumor of the nerve sheath that is comparatively rare in the oral cavity. The “Ancient” variant of neurilemomas presents a substantial diagnostic problem, whereas regular neurilemomas exhibit a characteristic biphasic pattern. A 65-year-old woman with a hard, painless lump on his lower lip is the subject of this case report. Significant nuclear atypia and hyperchromasia were found during the initial histopathologic evaluation, which raised the possibility of a spindle cell sarcoma. Nonetheless, a diagnosis of Ancient Neurilemoma was confirmed by the robust S100 positive and lack of mitotic features. This case emphasizes how crucial it is to identify degenerative changes in order to prevent needless, drastic surgery.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S359-S362